UPAYA MELATIH KEMAMPUAN MOTORIK ANAK DI KELOMPOK BERMAIN TERARAH HADLONAH DARUSSALAM PONOROGO - Siti Kasanah (QURROTI, 2020)
Motor development is one factor that isi so important in individual development and is associated with maturity and control of body movements. Basically every child’s motor development has differences, because sometimes there is something that can inhibit the development. Trerefore this research aims to find out the efforts made to rain the motor development of children in KBT Haadlonah Darussalam Ponorogo. this research uses descriptive qualitative research, with data collection techniques through observation, interviews, dan documentation. As for the results of this study, children are trained to be active and creative in the learning process with all activities such as drawing, coloring, and othets. While for barriers that occur such as the chid’s mood is not good, the child’s independence, the child’s ability to spesk and others.